Repurchase intention model for mobile shopping application users in Malaysia - Osmani, Mohammad (2022)
Mobile shopping applications have become a popular channel to reach the omnipresent consumer of today. However, the market space has become highly competitive and therefore, cultivating repurchase behaviour has become pivotal to retain market share and boost sustainability. While the literature regarding initial purchase via a mobile shopping application is well developed, knowledge on how to foster repurchase behaviour in this context is still scarce. The purpose of this research was to explore the consumers’ continuous behavioural intention towards using mobile shopping apps. More specifically, the study investigated to what extent does consumers’ continuance behavioural intention to purchase using mobile shopping applications is shaped by various factors. This study employed the Stimulus- Organism-Response (S-O-R) model as the theoretical framework as well as Delone and McLean’s Information System success model, Technology Acceptance Model (TAM), Expectation-Confirmation Model (ECM), Flow theory, and mobile featured factors to develop a research model based on a comprehensive literature review. Accordingly, factors of system quality, service quality, information quality, perceived usefulness, perceived ease of use, flow experience, perceived ubiquity, interactivity, perceived enjoyment, visual appeal (as Stimulus factors), satisfaction (as Organism factor), and repurchase intention and WOM intention (as Response factors) were included in the research model. In addition, flow experience was considered as the moderator factor on the relationships towards Response factors. In an attempt to examine the relationships between the dependent and independent variables, this study adopted a quantitative, cross-sectional approach, consistent with the positivist paradigm. A structured survey questionnaire was administered to a total of 240 consumers who had previously shopped via a mobile shopping application, using a non-probability purposive sampling approach. Partial least squares structural equation modelling (PLS-SEM) was used to test cause-effect relationships in the model. The results indicated that consumers’ satisfaction with mobile app was significantly explained by the factors of system quality, service quality, visual appeal, perceived ubiquity, perceived ease of use, perceived usefulness, and flow experience. Satisfaction significantly explained consumers repurchase intention and word-ofmouth (WOM) intention. Finally, the moderation analysis revealed that flow experience significantly moderated the relationships towards repurchase intention and WOM intention. This research provides a better insight for future researchers and organizations on continuous usage intention of mobile shopping apps.